Factors Associated With Within-Herd Transmission of Serotype A Foot-and-Mouth Disease Virus in Cattle, During the 2001 Outbreak in Argentina: A Protective Effect of Vaccination - Brito, B. P. (2011)
Argentina suffered an extensive foot-and-mouth disease (FMD) epidemic between July 2000 and January 2002, 3months after obtaining the official FMD-free without vaccination status conferred by the World Organization for Animal Health. This is one of the largest FMD epidemics controlled by implementation of a systematic mass vaccination campaign in an FMD-free country. In 2000, 124 herds were reported as FMD positive, 2394 herds in 2001 and one in January 2002; the total number of cattle herds in the country at that time was approximately 230000. Estimates of FMD transmission are important to understand the dynamics of disease spread and for estimating the value for the parameterization of disease transmission models, with the ultimate goals of predicting its spread, assessing and designing control strategies, conducting economic analyses and supporting the decision-making process. In this study, the within-herd coefficient of transmission, β, was computed for herds affected in the 2001 FMD epidemic and categorized as low or high based on the median value of β. A logistic regression model was fitted to identify factors significantly associated with high values of β. Results suggested that the odds of having a high within-herd transmission were significantly associated with time from initial herd infection to disease detection, date of report, vaccination, and time from initial herd infection to herd vaccination. Results presented in this study demonstrate, in quantifiable terms, the protective impact of vaccination in reducing FMD transmission in infected herds. These results will be useful for the parameterization of epidemiological models aimed at quantifying the impact of vaccination and for the design and implementation of FMD emergency vaccination strategies in face of an epidemic.